Digitalna transformacija nastavnog procesa u akademskoj muzičkoj edukaciji / Digital Transformation of the Teaching Process in the Academic Music Education - Akšamija, Valida; Ploskić, Nermin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
Nowadays, music education is facing with the process of accelerated digitalization of the teaching process, which is realized in limited technological and specific social circumstances. Given that the process is further complicated by the Covid-19 pandemic, teachers, as the main bearers of quality music education, more than ever, have the task, responsibility and obligation to adequately respond to the challenges of preparing, creating and applying various digital materials and teaching models. Regardless of the stated circumstances, the teachers had the obligation to fully realize the teaching process, while respecting the principles of quality and specifics of music teaching at the academic level. This posed a bigger challenge in the process of digitizing content and using different platforms and programs that could not always meet the set goal, tasks, outcomes and criteria of music education. The paper will present the results of research on the preparation, development and application of digital content and platforms in online teaching, difficulties in implementing the entire process, but also new ideas that could improve teaching in the time of digital transformation in music education. Teachers managed to meet the basic requirements of online teaching in a timely manner, but in the future it is necessary to allocate more time, space and investment for compulsory education in the field of digitalization, to be ready for new challenges in the teaching process in academic music education.